Teaching manual of color duplex sonography : a workbook on color duplex ultrasound and echocardiography - Hofer, Matthias; Antoch, G. (Gerald) ([Stuttgart ; New York] : Thieme)
Includes bibliographical references (p. 118-119) and index.